Effects of glucose on growth and health-promoting compounds in sunflower (Helianthus annuus L.) sprouts - Koodkaew, Intira; Issarawanich, Maysiyaporn (Agriculture and Natural Resources, 2019)
The increasing demand for healthy food products is increasing the pressure to enhance the beneficial phytochemicals in plants. The effects were investigated of glucose treatment on the growth, bioactive compounds and antioxidant capacity in sunflower sprouts. Application of 1,000 mM glucose reduced the fresh weight and increased the relative water content in sprouts but other concentrations (10 mM and 100 mM) had no effect on sprout biomass. Treatment with 100 mM and 1,000 mM resulted in an increase in the amount of flavonoid and radical scavenging activity. γ-Aminobutyric acid in sprouts treated with glucose increased in a dose-dependent manner. Treatment with 1,000 mM increased phenylalanine ammonia-lyase activity resulting in an increase in the phenolic compound content (61.24% higher than in the control sprouts). These results suggested that glucose solution could improve the functional composition and antioxidant property of sunflower sprouts.